2009
DOI: 10.1038/ijo.2009.38
|View full text |Cite
|
Sign up to set email alerts
|

A 4-year, cluster-randomized, controlled childhood obesity prevention study: STOPP

Abstract: Objective: To assess the efficacy of a school-based intervention programme to reduce the prevalence of overweight in 6 to 10-year-old children. Design: Cluster-randomized, controlled study. Subjects: A total of 3135 boys and girls in grades 1-4 were included in the study. Methods: Ten schools were selected in Stockholm county area and randomized to intervention (n ¼ 5) and control (n ¼ 5) schools. Low-fat dairy products and whole-grain bread were promoted and all sweets and sweetened drinks were eliminated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
150
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(160 citation statements)
references
References 39 publications
4
150
0
6
Order By: Relevance
“…A school-based intervention can reduce the prevalence of overweight and obesity in children and may affect eating habits at home 32 . Specifically, they recorded a decrease in the prevalence of overweight and obesity by 3.2% and 14.0%, respectively, after an intervention in which eating healthy food and being physically active was encouraged in five schools.…”
Section: Discussionmentioning
confidence: 99%
“…A school-based intervention can reduce the prevalence of overweight and obesity in children and may affect eating habits at home 32 . Specifically, they recorded a decrease in the prevalence of overweight and obesity by 3.2% and 14.0%, respectively, after an intervention in which eating healthy food and being physically active was encouraged in five schools.…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding figures for girls were 16-22% and 3-5%. These figures show a dramatic increase of overweight in 20 years (6,8,9).…”
Section: Facts About Overweight Obesity and Associated Co-morbiditymentioning
confidence: 93%
“…Similar to our study, they observed some positive trends in the healthy eating of the intervention group, which were not significant. Some other studies also did not observe any differences in healthy nutritional behaviors between the intervention and control groups after the nutrition education intervention (24)(25)(26). In previous studies, using behavioral changes models and theories resulted in acceptable changes in children, and their constructs can act as mediators to translate knowledge to behavior (27,28).…”
mentioning
confidence: 89%